Applications of Graphene-based electrocatalysts for PEMFCs. (2023) - Goyal, Priyanka; Ghosh, Avijit
Graphical abstract: Abstract: In light of the depleting fossil fuels, with rising concerns of energy security and climate change, alternate energy sources are being sought. Polymer electrolyte membrane fuel cells, which convert the chemical energy of fuel and oxygen to electricity are promising alternative clean sources of energy. The role of electrocatalysts is extremely significant in fuel cell performance. Widely used catalysts include Pt-based materials. Nonetheless, to make the fuel cells commercially viable, alternatives to Pt-based catalysts have been explored due to the high costs and low availability of Pt. Enhanced performance can be obtained when the catalysts are used along with supports. One such support that has gained significant attention and been explored for Pt loading is graphene, which has multiple advantages. Graphene can be used as a support for the loading of Pt nanoparticles or Pt-based alloys as well as non-noble metal-based catalysts. Graphene can be used alone as an electrocatalyst, without the incorporation of any metal catalyst as well, by methods such as functionalization, doping or preparation of hierarchical 3D structures with intercalating materials. All these have been shown to render the fuel cells highly performing as well as durable in long-term operation.